Validation of the Dutch version of the quick mild cognitive impairment screen (Qmci-D). Issue 1 (December 2015) - Bunt, Steven; O'Caoimh, Rónán; Krijnen, Wim; Molloy, D.; Goodijk, Geert; van der Schans, Cees; Hobbelen, Hans
Abstract Background Differentiating mild cognitive impairment (MCI) from dementia is important, as treatment options differ. There are few short (<5 min) but accurate screening tools that discriminate between MCI, normal cognition (NC) and dementia, in the Dutch language. The Quick Mild Cognitive Impairment (Qmci ) screen is sensitive and specific in differentiating MCI from NC and mild dementia. Given this, we adapted the Qmci for use in Dutch-language countries and validated the Dutch version, the Qmci -D, against the Dutch translation of the Standardised Mini-Mental State Examination (SMMSE-D). Method The Qmci was translated into Dutch with a combined qualitative and quantitative approach. In all, 90 participants were recruited from a hospital geriatric clinic (25 with dementia, 30 with MCI, 35 with NC). The Qmci -D and SMMSE-D were administered sequentially but randomly by the same trained rater, blind to the diagnosis. Results The Qmci -D was more sensitive than the SMMSE-D in discriminating MCI from dementia, with a significant difference in the area under the curve (AUC), 0.73 compared to 0.60 (p  = 0.024), respectively, and in discriminating dementia from NC, with an AUC of 0.95 compared to 0.89 (p  = 0.006). Both screening instruments discriminated MCI from NC with an AUC of 0.86 (Qmci -D) and 0.84 (SMMSE-D). Conclusion The Qmci -D shows similar, (good) accuracy as the SMMSE-D in separating NC from MCI; greater, (albeit fair), accuracy differentiating MCI from dementia, and significantly greater accuracy in separating dementia from NC. Given its brevity and ease of administration, the Qmci -D seems a useful cognitive screen in a Dutch population. Further study with a suitably powered sample against more sensitive screens is now required.